Acculturation of Islamic Culture in The Baayun Tradition in Sukamara Regency, Central Kalimantan - Rusliana, Lina; Ahmadi, Ahmadi (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2024)
The Baayun tradition is one of the cultural practices that remain sustainable in Sukamara Regency, Central Kalimantan. Acculturation between local culture and Islamic teachings in this tradition is an interesting topic to study. This research aims to analyze and describe the Baayun tradition of the Sukamara people as a form of the Living Qur'an. The research method used is qualitative, using semiotic analysis techniques, namely analyzing symbols, language, and actions in the procession. Data was obtained through interviews, observation, and documentation. The research results show that there is an intense syncretism process between local culture and Islamic teachings, resulting in a unique form of religious expression and reflecting the flexibility of Islam in adapting to local culture so that it becomes an integral part of community life.